First detection and molecular identification of Borrelia garinii spirochete from Ixodes ovatus tick ectoparasitized on stray cat in Taiwan. - Li-Lian Chao (Public Library of Science (PLoS), 2014)
Borrelia garinii spirochete was detected for the first time in Ixodes ovatus tick ectoparasitized on stray cat in Taiwan. The genetic identity of this detected spirochete was determined by analyzing the gene sequence amplified by genospecies-specific polymerase chain reaction assays based on the 5S-23S intergenic spacer amplicon (rrf-rrl) and outer surface protein A (ospA) genes of B. burgdorferi sensu lato. Phylogenetic relationships were analyzed by comparing the sequences of rrf-rrl and ospA genes obtained from 27 strains of Borrelia spirochetes representing six genospecies of Borrelia. Seven major clades can be easily distinguished by neighbour-joining analysis and were congruent by maximum-parsimony method. Phylogenetic analysis based on rrf-rrl gene revealed that this detected spirochete (strain IO-TP-TW) was genetically affiliated to the same clade with a high homogeneous sequences (96.7 to 98.1% similarity) within the genospecies of B. garinii and can be discriminated from other genospecies of Borrelia spirochetes. Interspecies analysis based on the genetic distance values indicates a lower level (<0.022) of genetic divergence (GD) within the genospecies of B. garinii, and strain IO-TP-TW was genetically more distant ( >0.113) to the strains identified in I. ovatus collected from Japan and China. Intraspecies analysis also reveals a higher homogeneity (GD<0.005) between tick (strain IO-TP-TW) and human (strain Bg-PP-TW1) isolates of B. garinii in Taiwan. This study provides the first evidence of B. garinii isolated and identified in an I. ovatus tick in Asia, and the higher homogeneity of B. garinii between tick and human strain may imply the risk of human infection by I. ovatus bite.